’The Influence of Corporate Governance Mechanisms and Company Size on the Integrity of Financial Reports - Puji, Utami (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Analysis This aiming For test influence ownership managerial , audit committee , commissioner independent , and size company to integrity report finance . The independent variable use ownership managerial , commissioner independent , audit committee and size company . While the dependent variable is integrity report finance . Data obtained from all company data transportation and logistics listed on the Indonesia Stock Exchange (IDX) in 2018-2022 , consisting of from 22 companies , and obtained 47 samples For processed . Analysis techniques multiple linear regression done For show influence variable independent to variable dependent . Analysis results show Ownership managerial No influential to integrity report finance , Commissioner independent influential negative and significant to integrity report finance , the audit committee is influential positive and significant to integrity report finance , and Size company influential negative and significant to integrity report finance .